Doxorubicin loaded carboxymethyl Assam bora rice starch coated superparamagnetic iron oxide nanoparticles as potential antitumor cargo. Issue 6 (June 2019) - Mohapatra, Sharmistha; Asfer, Mohammed; Anwar, Mohammed; Sharma, Kalicharan; Akhter, Mymoona; Ahmad, Farhan Jalees; Siddiqui, Anees Ahmad
Abstract: In recent years, polysaccharide-decorated superparamagnetic iron oxide nanoparticles (SPIONs) have gained attention in the field of "nanotheranostics" with integrated diagnostic and therapeutic functions. Carboxymethyl Assam bora rice starch-stabilized SPIONs (CM-ABRS SPIONs), synthesized by co-precipitation method, has already shown exciting potential towards magnetic drug targeting potential. After establishing it as a promisable targeting carrier, the present study is focused on the next step i.e. to evaluate its In vitro anti-tumor potential by loading anticancer drug "Doxorubicin hydrochloride (DOX)" onto CM-ABRS SPIONs. DOX-loaded CM-ABRS SPIONs were physico-chemically characterized by DLS, zeta-potential, TEM, FT-IR, XRD, and VSM analysis. Spectroflourimetric analysis confirmed the maximum loading of DOX up to 6% (w/w) onto CM-ABRS SPIONs via electrostatic interactions. Further, molecular level drug performance was investigated by docking study against receptors (HER-2 and Folate receptor-α) over expressed in cancer cells and MTT assay (in MCF-7 and HeLa cell line), which conferred promisable results of DOX-CM-ABRS SPIONs as compared to standard DOX solution.